MAKING RURAL SCHOOLS MORE USEFUL FOR THE COMMUNITY; PREVENTION OF BRAIN DRAIN - Sugiono Sugiono (PEDAGOGIK : JURNAL PENDIDIKAN, 2017)
Rural schools in Indonesia face various problems that are uniquely rural. A comprehensive report on rural schools in Indonesia has found high rates of poverty and low levels of educational attainment (Improving People’s Access Towards More Qualified Education 2004). It has found that rural schools are staffed by younger, less well-educated faculty members and administrators, who earn low salaries and benefits compared to their urban or metropolitan counterparts. The report also documents persistent problems related to rural school finance, teacher compensation and quality, facilities, curriculum, and student achievement.